2017
DOI: 10.15578/bawal.3.3.2010.191-197
|View full text |Cite
|
Sign up to set email alerts
|

Fekunditas Dan Diameter Telur Ikan Terbang Di Perairan Selat Makassar Dan Utara Bali

Abstract: ABSTRAKFekunditas dan diameter telur ikan merupakan bagian dari studi reproduksi biologi perikanan. Aspek ini dikaji dari tiga jenis ikan terbang, yaitu Cheilopogon cyanopterus, Hirundichthys oxycephalus, dan Parexocoetus mento yang dikumpulkan dari hasil tangkapan nelayan dengan jaring insang hanyut di perairan Takalar (Selat Makassar) dan Pemuteran (Bali Utara). Jumlah contoh yang diamati 58 gonad ikan betina yang berada pada tingkat kematangan gonad III dan IV. Fekunditas tertinggi dimiliki oleh Parexocoetu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Flying fish, including pelagic fish, which live on the open ocean's surface, can jump out of the water and glide for great distances. Flying fishes are members of the family Exocoetidae (Parin 1996;Carpenter and Niem 1999;Carpenter and Niem 2001), composed of 71 valid species (Wu et al 2017), 18 of which were found in Indonesia (Robins and Ray 1986;Shen 1993;Sommer and Poutiers 1996;Parin 1999;Carpenter and Niem 2001;Riede 2004;Febyanty and Syahailatua 2008;Ferdiansyah and Syahailatua 2010;Fricke and Wantiez 2011). Flying fish, is one of important species in South Sulawesi waters, especially in Makassar Strait and Flores Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Flying fish, including pelagic fish, which live on the open ocean's surface, can jump out of the water and glide for great distances. Flying fishes are members of the family Exocoetidae (Parin 1996;Carpenter and Niem 1999;Carpenter and Niem 2001), composed of 71 valid species (Wu et al 2017), 18 of which were found in Indonesia (Robins and Ray 1986;Shen 1993;Sommer and Poutiers 1996;Parin 1999;Carpenter and Niem 2001;Riede 2004;Febyanty and Syahailatua 2008;Ferdiansyah and Syahailatua 2010;Fricke and Wantiez 2011). Flying fish, is one of important species in South Sulawesi waters, especially in Makassar Strait and Flores Sea.…”
Section: Introductionmentioning
confidence: 99%